Raw materials prices under pressure - Heinz Kolbe (Intereconomics, 1984)
Since April 1984 there has been a general fall in world market prices for industrial raw materials following upon increases which, in some cases, had been quite considerable. What are the reasons for this development? What are the prospects for 1985?
Keywords: 330